Integrated Elements of Paragraph in UNISBA Student’s Writing - Nuranisa Dewi, Asri; Pratikno, Heru; Yulita Silviany, Irma (KnE Social Sciences, 2023)
Writing a scientific paper cannot be separated from academic activities carried out by students. In writing, they must apply the requirements of good paragraphs so they can be understood by the reader. One of the requirements for making a good paragraph is to combine the elements in it. However, in reality, there are still many students who have not paid attention to and applied these requirements in their writing. Therefore, this study aims to determine the extent of the suitability of the writings made by students with the given topic. In addition, it will help us in understanding if there has been good coherence between the ideas. The method used in this research is the descriptive quantitative method. The source of this research data is taken from the Google Form which must be filled out by students about writing. This study hypothesized that the students were able to write a good paragraph based on logical thinking, on a given topic. However, some of their writings are still not related to the elements of the paragraph. Thus, there is a need for writing classes or special guidance for students in improving their writing, especially in logical thinking. This will help us in finding out if there are any fallacies in their writing. This activity is very important, to do so that students’ writing can be better and of higher quality, both in terms of Indonesian grammar rules and logical thinking. Keywords: paragraph coherence, writing, logical fallacy